PERLINDUNGAN HUKUM TERHADAP KEBEBASAN BERPENDAPAT MELALUI MEDIA INTERNET BERDASARKAN UNDANG-UNDANG NO.11 TAHUN 2008 TENTANG INFORMASI DAN TRANSAKSI ELEKTRONIK DI TINJAU DARI PERSPEKTIF HAM - Darlisma Darlisma; Ernawati Ernawati (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2022)
This legal research aims to find out about the legal protection of freedom of expression through the internet as regulated in Law no. 11 of 2008 concerning Information and Electronic Transactions from the perspective of Human Rights. The problems raised in this study are (1) What are the limitations on freedom of expression through the internet according to Law No. 11 of 2008 and the Human Rights Perspective? (2) Does the protection of freedom of expression in Law No. 11 of 2008 contradict the freedom of expression in human rights? The method used in this research is the normative juridical method. Sources of data used include primary legal materials, secondary legal materials. Data collection techniques used are library research and cyber media. The data obtained is then analyzed by grammatical interpretation and systematic interpretation of the provisions contained in the ITE Law. The results of the study indicate that law no. 11 of 2008 concerning Information and Electronic Transactions cannot be said to have protected freedom of expression.